Rintisan Desa Cerdas (RDC) melalui Program Pemberdayaan Masyarakat Desa Bakti Kecamatan Pulubala Kabupaten Gorontalo Provinsi Gorontalo - Arwildayanto Arwildayanto; Setyo Utoyo (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
The goal of the Smart Village Pilot (RDC) in Bakti Village, Pulubala District of Gorontalo Regency conducted by Gorontalo State University students following the Sibermnas Lecture (KKS) work program is to transform mindsets, ways of working in the community to improve quality of life, economy, skills, expertise, management and governance village governance supported by innovation and technology transfer. The KKS method is carried out using community empowerment techniques by students interactively related to indicators towards RDC. Programs that have been implemented involve stakeholders, including training on village government financial governance, with the Head of the Gorontalo Province Regional Treasury Office, training on village governance by the KKS Supervisor, Socialization of maternal and child health, enhancing creative economy through the use of the environment for Family Medicinal Plants together with the Chairperson of PKK District. Gorontalo, Socialization of Basic Rights of Children, Community Protection from HIV/AIDS and Cervical Cancer by the Chairperson of the Child Protection Commission, Chairperson of the HIV/AIDS Assistant Team and Chairperson of the Gorontalo Province PKK Movers Team, Greening and planting of plant seedlings productive by the Central Watershed Management and Protection Forest District. Bone Bolango, Improved internet network infrastructure by the Gorontalo Telkomsel, Smart Cars by FIP UNG, trash bins by the Gorontalo Provincial Treasury Regional Office.